2006
DOI: 10.1007/s00384-006-0102-0
|View full text |Cite
|
Sign up to set email alerts
|

The effects of low-frequency endo-anal electrical stimulation on faecal incontinence: a prospective study

Abstract: Low-frequency endo-anal electrical stimulation significantly improves continence scores and quality of life in patients with faecal incontinence not amenable to surgical correction. It leads to improved manometric values when carried out on a daily basis with a portable home unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…Twenty-three studies were retrospective chart reviews or prospective case series [ 37 59 ], and four current trials [ 60 – 63 ] were found in trial registries, but not in the literature. Seven RCTs [ 15 , 64 69 ] met at least one exclusion criterion (Supplementary Table S 2 ), and 13 RCTs remained [ 11 , 14 , 16 , 18 , 70 78 ] (Supplementary Tables S 3 to S 5 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-three studies were retrospective chart reviews or prospective case series [ 37 59 ], and four current trials [ 60 – 63 ] were found in trial registries, but not in the literature. Seven RCTs [ 15 , 64 69 ] met at least one exclusion criterion (Supplementary Table S 2 ), and 13 RCTs remained [ 11 , 14 , 16 , 18 , 70 78 ] (Supplementary Tables S 3 to S 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…It was also neglected in some two-group randomized trials where two ES stimulations were compared and both ES were below the threshold for effectiveness [ 13 ]. Stimulation with alternating current at medium frequency (MF > 1,000 Hz; amplitude-modulated medium frequency: AM-MF), also termed pre-modulated interferential ES in the literature, does not have the disadvantage of LFS because its biological effect is based on a different principle than the all-or-nothing effect of LFS [ 16 ]. Previous systematic reviews [Supplementary Table S 1 ; 17 – 19 ] did not distinguish between LFS and MF therapies.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Healy et al in 2006 randomized 48 patients to endoanal electrical stimulation with a home unit versus endoanal electrical stimulation plus augmented biofeedback under supervision of a physical therapist. 41 Both groups improved in terms of continence scores, manometric pressure readings posttreatment, and quality of life.…”
Section: Summary Of Selected Trials Involving Electrical Stimulation mentioning
confidence: 88%
“…Low frequencies (10-20 Hz) are used to treat urge incontinence and high frequencies (35-50 Hz) are used to treat stress incontinence 6. Little is known, however, about the effectiveness of EST using anal plugs in anorectal functional disorders, especially in patients with fecal incontinence 7,8,12…”
Section: Discussionmentioning
confidence: 99%
“…As EST may rehabilitate the pelvic floor muscle, it has been tested in defecation disorders. EST using an anal plug has been shown successful in up to 60% of patients with fecal incontinence 7,8…”
Section: Introductionmentioning
confidence: 99%